2011
DOI: 10.1242/dev.067587
|View full text |Cite
|
Sign up to set email alerts
|

Pax7-expressing satellite cells are indispensable for adult skeletal muscle regeneration

Abstract: There was an error published in Development 138, 3647-3656.The panel labels on the left indicating genotypes were misaligned in Fig. 5A. The corrected Fig. 5 appears in full below.The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
519
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(542 citation statements)
references
References 56 publications
21
519
0
2
Order By: Relevance
“…These results are not in contradiction with those reported here for the following reasons: the ablation of Pax7 + satellite cells was carried out in adult mice, at an age when the contribution of AP + pericyets to muscle regeneration becomes negligible. It is also possible that satellite cells are required to induce other cell types to adopt a myogenic fate, as suggested by Sambasivan et al 48 In conclusion, we have demonstrated that vascular pericytes, resident in skeletal muscle, are bi-potent (as confirmed by clonal analysis), as they contribute to both the smooth muscle layer of blood vessels and skeletal muscle fibre development, including the satellite cell pool, during unperturbed, postnatal growth of the mouse. It is still unknown how this choice is regulated in vivo, although it is plausible that signals emanating from neighbour muscle fibres or endothelium may direct the cells to a skeletal or to a smooth muscle fate, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are not in contradiction with those reported here for the following reasons: the ablation of Pax7 + satellite cells was carried out in adult mice, at an age when the contribution of AP + pericyets to muscle regeneration becomes negligible. It is also possible that satellite cells are required to induce other cell types to adopt a myogenic fate, as suggested by Sambasivan et al 48 In conclusion, we have demonstrated that vascular pericytes, resident in skeletal muscle, are bi-potent (as confirmed by clonal analysis), as they contribute to both the smooth muscle layer of blood vessels and skeletal muscle fibre development, including the satellite cell pool, during unperturbed, postnatal growth of the mouse. It is still unknown how this choice is regulated in vivo, although it is plausible that signals emanating from neighbour muscle fibres or endothelium may direct the cells to a skeletal or to a smooth muscle fate, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Very recently, three reports [46][47][48] showed that selective ablation of Pax7-expressing satellite cells during adult life permanently hampers subsequent attempts to regenerate skeletal muscles, leading to the conclusion that no other endogenous cell types may substitute for satellite cells. These results are not in contradiction with those reported here for the following reasons: the ablation of Pax7 + satellite cells was carried out in adult mice, at an age when the contribution of AP + pericyets to muscle regeneration becomes negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite cells are specialized myogenic stem cells that are located beneath the basement membranes of muscle fibers and are required for muscle regeneration and growth (Sambasivan et al, 2011). In response to injury, satellite cells exit their quiescent state and then proliferate, differentiate, and fuse with existing myofibers to provide new myonuclei and replace or repair injured cells (Relaix & Zammit, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…satellite cells) located between the basal lamina and sarcolemma (Mauro, 1961). Resident satellite cells normally exist in a mitotically quiescent state in adult muscle, but re-enter the myogenic program in response to regenerative cues such as mechanical loading, injury, or disease (Lepper et al, 2011;Sambasivan et al, 2011). Activated satellite cells may then proliferate nominally to repair small localized damage, fuse together to form myofibers in the face of considerable muscle injury, or provide additional nuclei to support myofiber expansion (Adams, 2006;Kook et al, 2006;Le Grand and Rudnicki, 2007).…”
Section: Introductionmentioning
confidence: 99%